MYOMA OF THE ROUND LIGAMENT MIMICKING THE CLINICAL APPEARANCE OF THE INGUINAL HERNIA – A CASE REPORT - Aleš Pišek (Zdravniški Vestnik, 2004)
Background. Myomas are the most frequent gynecological tumors. They first occur during puberty; however, they are most frequent among aged between 35 and 50. In this age group their incidence is 15–20%. They are rare after menopause. The majority of myomas arise in the uterus, but they may arise from other extrauterine sites such as the fallopian tubes, ovaries, round ligament, ligamentum latum, sacrouterine ligament, vagina and even the urethra. Most authors agree that there are numerous causes for the occurrence of myomas; however, they have not yet been clearly proven. They however agree that the myomas appear most frequently in the reproductive age, when the ovarian hormone levels are high and they diminish after menopause. They equally agree that the risk factors for the clinically significant myomas are nulliparity, obesity, a positive family history of myomas and African racial origin. Patients and methods. A 43-year-old patient was referred to our institution for operative treatment by her personal gynaecologist who clinically and sonografically verified a solid tumor situated to the right side of the uterus. The size of the tumor was that of a newborn’s head. The patient, however, had been observing a reponible inguinal hernia the size of a female fist for a period of four years. A solid tumor (22×6×7 cm) arising from the right round ligament, was remowed during surgery. Half of its size was situated in the inguinal canal thus mimicking the clinical appearance of the inguinal hernia. After the tumor was removed the inner door of the inguinal canal closed by itself, no surgical repair was necessary. On histological examination the tumor was classified as a leiomyoma. Conclusions. Although the leiomyoma of the round ligament is the most frequent tumor of that region it is a rare gynecological tumor. The described case is especially interesting due to the unusual position of the tumor. It was situated partly intraabdominally and partly inside the inguinal canal, thus mimicking the clinical appearance of the inguinal hernia.